Accompagner les familles : les « savoir-faire discrets » des Enseignants référents - Matthieu Laville (Université de Provence, 2018)
Since the beginning of the 2006 academic year, Teacher-referents have been responsible for the academic journey of pupils with disabilities. In the interests of educational inclusion, they must continue to favour the links between actions taken by the educational team and those taken by the health and social care providers. The Teacher-referents are also the privileged voice of the families throughout the academic journey of their children. Consistent with the theories of "care", this article proposes to update the "discreet know-hows" put to work by these professionals towards families of disabled children. Analysis of a collection of semi-directive interviews conducted with around 21 Teacher-referents allows us to show that the use of "care" in the accompaniment of these families consists of genuine work behind the scenes which slips into the folds of their activities. This analysis asks us to question ourselves on the possibilities and on the pertinence of increasing the visibility of the "care" work of the Teacher-referents.